Cutaneous angiosarcoma treated with taxane‐based chemoradiotherapy: A multicenter study of 90 Japanese cases. Issue 1 (8th November 2022) - Fujimura, Taku; Furudate, Sadanori; Maekawa, Takeo; Kato, Hiroshi; Ito, Takamichi; Matsushita, Shigeto; Yoshino, Koji; Hashimoto, Akira; Muto, Yusuke; Ohuchi, Kentaro; Amagai, Ryo; Kambayashi, Yumi; et al.
Abstract: Cutaneous angiosarcoma (CAS) is rare and most previous studies of CAS have been small case series, and randomized, phase II studies of CAS are limited. Since treatment options for CAS are controversial, and because only paclitaxel should be recommended based on high‐level evidence, it is important to evaluate the efficacy of another taxane‐derived agents, docetaxel, in real‐world practice. The efficacy and safety profiles of chemoradiotherapy using taxane‐based agents, docetaxel and paclitaxel, were retrospectively examined in the maintenance setting in 90 Japanese CAS patients, including 35 docetaxel‐treated cases and 55 paclitaxel‐treated cases. Overall survival and dose duration time of the patient group treated with docetaxel was equivalent to that with paclitaxel, even in the cohorts with metastasis. Adverse events due to docetaxel and paclitaxel were observed in 77.1% and 69.1% of cases, respectively. The incidence ratio of total severe adverse events tended to be higher in the docetaxel‐treated group (40.0%) than in the paclitaxel‐treated group (23.6%). Peripheral neuropathy occurred only in the paclitaxel‐treated group, whereas high‐grade interstitial pneumonia developed only in the docetaxel‐treated group. In addition, we also evaluate 19 patients selected other taxanes, 17 patients selected eribulin methylate, 11 patients pazopanib, and 2 patients selected nivolumab as second‐line chemotherapy. The efficacy of a monthly docetaxel regimen is equivalent to a three‐weekly paclitaxel regimen evaluated by Overall survival and DDT, even in the cohorts with metastasis, and it is a tolerable protocol for CAS as a maintenance therapy in the Japanese population. Abstract : Although paclitaxel is given as a standard therapy for the treatment of cutaneous angiosarcoma (CAS), subsequent treatment for CAS is limited and still controversial. Several chemotherapy regimens were tentatively used for the treatment of CAS.In this report, the efficacy and safety profiles of monthly docetaxel regimen and a three‐weekly paclitaxel regimen in the maintenance setting after curative radiotherapy were evaluated retrospectively in 90 Japanese CAS patients. Our present study suggested that the efficacy of a monthly docetaxel regimen is equivalent to a three‐weekly paclitaxel regimen evaluated by OS and DDT, and is a tolerable protocol for CAS as a maintenance therapy.